Design and development of unmanned aerial vehicle (Drone) for civil applications - Bappy, A.M. Reasad Azim; Md. Asfak-Ur-Rafi; Islam, Md. Saddamul; Sajjad, Ali; Imran, Khan Nafis (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2015.